Strontium doped calcium phosphate coatings on poly(etheretherketone) (PEEK) by pulsed electron deposition - Bianchi, Michele; Degli Esposti, Lorenzo; Ballardini, Alberto; Liscio, Fabiola; Berni, Matteo; Gambardella, Alessandro; Leeuwenburgh, Sander C.G.; Sprio, Simone; Tampieri, Anna; Iafisco, Michele (Surface & coatings technology, 2017)
Herein the preparation of Sr2+-doped calcium phosphate (CaP) coatings on poly(etheretherketone) (PEEK) substrates by pulsed electron deposition (PED) was investigated. Hydroxyapatites (HA) substituted with tailored amounts of Sr2+ up to 9wt% were synthesized to generate the deposition targets. Dense and uniform amorphous CaP films having Sr/Ca molar ratios close to that of targets were achieved. The roughness and the wettability of the bare PEEK were significantly enhanced after coating deposition. The presence of Sr2+ led to a slight increase of the particles size while it did not mainly affect the RMS of the coatings that consisted of nanostructured aggregates of globular shape. After a mild annealing treatment at 130°C for 6h, the amorphous coatings transformed into nanocrystalline HA films incorporating Sr2+ having Sr/Ca molar ratios close to those of the as-deposited films. The annealing did not affect the topography and the roughness of the coatings, while improved the hardness of the films un-doped and doped at low-extent. This study shows that PED is feasible technique to coat PEEK implants with CaP films with control over the Sr/Ca ratio, which could improve bone fixation and in vivo stability especially under osteoporotic conditions thanks to the anabolic effect of Sr2+. [Display omitted] •HA doped with tailored amount of Sr2+ were prepared to generate targets.•As-deposited CaP films are amorphous having Sr/Ca molar ratios close to those of targets.•A mild annealing converts amorphous films into nanocrystalline HA incorporating Sr2+.•The Sr/Ca molar ratio of the coatings after annealing is preserved.•Roughness and wettability of bare PEEK are enhanced after coating deposition.